Reconstruction of the third phalanx of the subamputed ring finger of a 10-year-old girl - Meccariello Luigi; Cioffi Sara; Pagliantini Claudio; Bartoleschi Eugenio; Di Giacinto Salvatore; D`ascola Jacopo (Scripta Medica, 2014)
A ten-year-old patient came under the observation of the U.O. OrtopediaUniversitaria of the A.O.U. Policlinico Santa Maria AlleScotte. She reported the following diagnosis: hyperflexion of the third phalanx of the left hand fourth finger, with hypogenesis of the third phalanx. As the first of the three surgical phases proposed, the patient underwent the retensioning of the long flexor tendon of the fourth finger and kinesis exercises in order to rehabilitate the phalanx correctly.